The role of nuclear in China's energy future: Insights from integrated assessment. (April 2020) - Yu, Sha; Yarlagadda, Brinda; Siegel, Jonas Elliott; Zhou, Sheng; Kim, Sonny
Abstract: China, the world's largest electricity consumer, has strong motivations to deploy nuclear power due to increasing electricity demand and environmental concerns. However, there are social, institutional, and technical barriers to future nuclear expansion. This paper provides an updated assessment of nuclear energy potential in China with analyses at both national and provincial levels and compares results with previous studies. It integrates unit-level information into integrated assessment modelling and scenarios and considers the interactions among different socioeconomic pathways, technology options, climate policies, and social/political concerns on inland siting. Among all factors explored, climate policies have the most significant impact on accelerating nuclear technology deployment. Inland siting of nuclear power plants increases total capacity, but the impact is limited without climate policy. The share of annual nuclear generation across scenarios/studies is unlikely to rise above 11% by 2030 and 30% by 2050 of total Chinese electricity generation. A dramatic increase in total nuclear power generation in China – around 4000 TWh of nuclear generation by 2050 – is only possible in scenarios where China sees electricity demand increase substantially, sticks to and tightens its current Paris Accord commitments, achieves low costs of nuclear technologies, and allows inland siting of nuclear power plants. Highlights: China is unlikely to meet 2020 nuclear deployment and construction targets. Climate policies have the largest impact on accelerating nuclear power in China. Expanding inland nuclear deployment would increase total capacity in a limited way. The share of nuclear generation is up to 11% by 2030 and 30%, by 2050. Rapid growth in nuclear is possible with high demand, low cost, and strong policy.